2020
DOI: 10.1186/s12872-020-01794-6
|View full text |Cite
|
Sign up to set email alerts
|

Controlled direct effect of psychiatric disorders on cardiovascular disease: evidence from a large Kurdish cohort

Abstract: Background Psychiatric disorders are significantly associated with the incidence and prevalence of cardiovascular diseases, mortality, hospital readmissionn. Oral and dental hygiene may play a role in such association. This study aimed to evaluate the controlled direct effect of psychiatric disorders on cardiovascular diseases by controlling the mediating effect of oral and dental hygiene. Methods The data used for this study came from the baseline phase of Ravansar Non-communicable Disease (RaNCD) cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…With the development of the biopsychosocial model, more and more researchers have found a close link between psychological factors and CVD (21). Studies have shown that MD may be an independent risk factor for CVD (22). They increase the morbidity and mortality of CVD patients and reduce the quality of survival in CVD patients (22,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of the biopsychosocial model, more and more researchers have found a close link between psychological factors and CVD (21). Studies have shown that MD may be an independent risk factor for CVD (22). They increase the morbidity and mortality of CVD patients and reduce the quality of survival in CVD patients (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that MD may be an independent risk factor for CVD ( 22 ). They increase the morbidity and mortality of CVD patients and reduce the quality of survival in CVD patients ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…This analysis and research method has the same idea as many other articles, which can ensure the reliability of the research results. [16][17][18] From the perspective of social medicine and social psychology, prolonged chronic diseases may break the life balance of individuals. When the coping mechanism is ineffective, individuals live with depression, anxiety, sleep disorders, and other symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is noteworthy that well‐known cardiac risk factors such as aging and obesity can explain only half of the causes of clinical CVDs 5 . On the other hand, a growing body of evidence has emphasized the substantial role of psychological disorders, especially depressive disorder, anxiety states, including panic disorder, post‐traumatic psychological symptoms, and mental stress in the development of CVDs 6–8 . To some extent, poor outcomes of patients with CVDs and concomitant psychological disorders have made them the subjects of much recent research in this era 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“… 5 On the other hand, a growing body of evidence has emphasized the substantial role of psychological disorders, especially depressive disorder, anxiety states, including panic disorder, post‐traumatic psychological symptoms, and mental stress in the development of CVDs. 6 , 7 , 8 To some extent, poor outcomes of patients with CVDs and concomitant psychological disorders have made them the subjects of much recent research in this era. 9 , 10 Depression in patients with congestive heart failure (CHF) has an independent prognostic role in patients' outcomes and can promote about two to three‐fold higher rates of re‐hospitalization and mortality.…”
Section: Introductionmentioning
confidence: 99%